1956
DOI: 10.2170/jjphysiol.6.226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Sulfhydryl Reagents on the Mechanical and Electrical Activity of the Toad's Heart

Abstract: Recently, attention of many investigators has been directed to the physiological significance of the protein sulfhydryl (SH) group in various tissues. In the heart, too, the solution of this problem was pursued by several workers (1,2,3,4,5). The effect of cadmium chloride on the electrical activity of the frog's heart was reported by Logunova and Kipershlak (4), who postulated that the electrocardiographic changes with cadmium chloride was due to a binding of the protein sulfhydryl (SH) groups. Afterwards, Kl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1958
1958
1979
1979

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A few investigators (KLEINFELD et al, 1955;TAKAHASHI et al, 1956;KLEINFELD and STEIN, 1968;HAYASHI and HORIUCHI, 1971 a;TODA, 1973) have hitherto described the effects of Cd on the cardiac muscle, but none has tried to study the Cd effect in relation to pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few investigators (KLEINFELD et al, 1955;TAKAHASHI et al, 1956;KLEINFELD and STEIN, 1968;HAYASHI and HORIUCHI, 1971 a;TODA, 1973) have hitherto described the effects of Cd on the cardiac muscle, but none has tried to study the Cd effect in relation to pH.…”
Section: Discussionmentioning
confidence: 99%
“…This process is considered to be pH-dependent. However, most Cd-uptake into cardiac muscle is pH-independent and may be nonspecific to contraction.Effects of cadmium (Cd) on the electrical and mechanical activities of cardiac muscle in normal pH solution have been studied (KLEINFELD et al, 1955;TAKAHASHI et al, 1956;KLEINFELD and STEIN, 1968;HAYASHI and HORIUCHI, 1971a;TODA, 1973). It was found that a low concentration of Cd (about 10 /AM) brought about a decrease in contractility without an appreciable change in the action potential, and this Cd effect on contractility was completely antagonized by excess Ca (HAYASHI and HORIUCHI, 1971a).…”
mentioning
confidence: 99%